The Construction of Culture Based on Local Wisdom in the Lives of Hizbut Tahrir and Ahmadiyya Followers in Konawe Selatan Regency - Anggraini, Dewi; Zanynu, Muhammad Aswan (Universitas Muhammadiyah Sidoarjo, 2013)
This study aims to investigate the implementation of religious life between Hizbut Tahrir and Ahmadiyah followers in South Konawe. The Islamic doctrines they understand influence the behavior of Hizbut Tahrir in religious life againstAhmadiyah followers in South Konawe. This study uses a qualitative along with phenomenological approach and there are two locations as the concentrations of the two beliefs: Wolasi in Ranowila village and Konda in Lamomea village. Islamic doctrines that affect the behavior of Hizbut-Tahrir religious life against Ahmadiyah followers in South Konawe are: a). Organizational Vision, b). Thought Reference Sources, c). Products Interpretation, d) method. The creation of peace between Hizbut Tahrir and Ahmadiyah followers in South Konawe can not be separated from the following aspects: a). Graphic of Socio Religious as Local Tolerance Portraits, b). Houses of Worship as Symbols of Harmony and Tolerance Awareness, c). Elite Communication Network of Hizbut Tahrir and Ahmadiyah, d). Propagation Methods and Strategic Goals.